Disclosure of HIV status among Shan female migrant workers living with HIV in Northern Thailand: A qualitative study - Arratee Ayuttacorn (2019)
© 2019 Ayuttacorn et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background Disclosure of HIV status is a critical gateway to HIV prevention. Despite many studies on this topic, there is a gap in knowledge regarding HIV status disclosure and risky sexual behavior in HIV-infected female migrant workers. The current study addressed this research gap, and focused on HIV-infected Shan female migrant workers in Northern Thailand. Methods This study conducted in-depth interviews with 18 HIV-infected Shan female migrants (aged between 23–54 years old) and 29 healthcare workers in district hospitals in Chiang Mai. Content analysis was employed to identify particular themes related to HIV status disclosure, sexual risk behavior, and ART adherence. Results We found that non-disclosure to husbands/partners was mostly related to fear of marital conflict and of losing social and financial support. Non-disclosure prevented Shan female migrant workers from negotiating condom use with their partners. Reasons for not disclosing to friends, family and other community members were mostly related to feared rejection and discrimination due to HIV-related stigma. Accounts of condomless sex in the context of HIV status disclosure suggest that gender norms and male dominance over women influenced decision-making for safe sex. Lastly, some female migrant workers perceived low risk of HIV transmission with good adherence to the ART. Conclusions This study highlighted the complex challenges of HIV status disclosure among HIV-positive Shan female migrant workers and the link between disclosure/non-disclosure and condom use. There is a pressing need to create realistic disclosure mechanisms that take into account the socio-cultural barriers to disclosure including marital conflicts, stigma, and gender norms. Messages to encourage condom use should be delivered carefully so that knowledge of the HIV transmission reduction qualities of good ART adherence does not serve as a barrier to condom use.